Emergency Medicine Resident versus Radiologist in Detecting the Ultrasonographic Signs of Acute Cholecystitis; a Diagnostic Accuracy Study - Tootian Tourghabe, Javad; Arabikhan, Hamid Reza; Alamdaran, Ali; Zamani Moghadam, Hamid (Archives of Academic Emergency Medicine, 2018)
Introduction: Dependence of ultrasonography on the operator’s skill plays a major role in the differences between various studies in reporting its diagnostic accuracy. Therefore, the present study was done with the aim of comparing the ultrasonography findings performed by emergency medicine resident and radiologist in evaluation of acute cholecystitis. Methods: The present diagnostic accuracy study has been carried out on patients presenting to the emergency department with complaint of pain in the right upper quadrant of abdomen suspected with acute cholecystitis. All the patients underwent gallbladder ultrasonography by a trained emergency medicine resident and a radiologist and their findings were compared with surgical and pathology findings regarding gallstone and increased gallbladder wall thickness. Results: 51 patients with the mean age of 42.3±15.8 (17-81) years were analyzed (82.4% female). The overall agreement between emergency medicine resident and radiologist in ultrasonographic diagnosis of cholecystitis was 0.421 (95% CI: 0.118-0.724). Based on the pathology and surgical findings, acute cholecystitis was confirmed for all 51 (100%) patients. Meanwhile, based on the ultrasonographic report of radiologist and emergency medicine resident only 45 (88.2%) and 34 (66.7%) patients, respectively, were diagnosed with cholecystitis. Screening performance characteristics of ultrasonography by radiologist for detection of gallbladder stone (p = 0.010) and gallbladder wall thickness (p < 0.0001) were significantly better than emergency medicine resident. Conclusion: The screening performance characteristics of ultrasonography by radiologist in detection of gallstones and increased wall thickness of gallbladder were significantly better.